Natural Killer Cells in Afferent Lymph Express an Activated Phenotype and Readily Produce IFN-γ - Lund, Hege; Boysen, Preben; Hope, Jayne C.; Sjurseth, Siri K.; Storset, Anne K. (Frontiers in Immunology, 2013)
Natural killer (NK) cells are motile cells that migrate between peripheral blood (PB), lymph nodes (LNs) and various organs. Domestic animals have frequently been used to study cellular migration, and offer unique opportunities for such studies. The aim of this study was to characterize the phenotype and cytokine producing capacity of NK cells in bovine skin-draining lymph. NKp46/NCR1+ CD3- cells constituted 2-11 % of mononuclear cells in afferent lymph (AL), a majority of cells were CD16+, CD8α+ and CD2-/low, and elevated CD25 and CD44 expression indicated an activated phenotype. Interestingly, significantly fewer AL NK cells expressed the early activation marker CD69 compared to PB NK cells. A large proportion of lymph and blood NK cells produced interferon (IFN)-γ following stimulation with IL-2 and IL-12. Notably, in AL, but not blood, a similar amount of IFN-γ+ NK cells was observed when cells were stimulated with IL-12 alone. Overall, AL NK cells were more similar to LN-residing NK cells than those circulating in PB. We conclude that AL appears to be an important migration route for tissue-activated NK cells, and may represent an alternative route for NK cell traffic to LNs. These findings may have important implications in the development of adjuvant strategies that aim to target NK cells in a vaccine response.